2018
DOI: 10.1039/c8nj02594k
|View full text |Cite
|
Sign up to set email alerts
|

The peroxidase-like catalytic activity of ferrocene and its application in the biomimetic synthesis of microsphere polyaniline

Abstract: Ferrocene can be used as a peroxidase mimic to catalyze 3,3′,5,5′-tetramethylbenzidine or aniline oxidation in the presence of H2O2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…For some nanoparticles, the onset of microphase separation becomes visible due to the presence of ferrocene units in the hydrophobic block. The membrane thickness is characteristic of the bilayer membrane in polymersomes, prepared by RAFT polymerization, confirming the general formation of the desired polymeric vesicles . Additionally, also vesicle diameters for F c 1B Psomes could be determined by SEM measurements, but with larger diameters (⌀ 142 ± 25 nm; Figure ).…”
Section: Resultssupporting
confidence: 58%
“…For some nanoparticles, the onset of microphase separation becomes visible due to the presence of ferrocene units in the hydrophobic block. The membrane thickness is characteristic of the bilayer membrane in polymersomes, prepared by RAFT polymerization, confirming the general formation of the desired polymeric vesicles . Additionally, also vesicle diameters for F c 1B Psomes could be determined by SEM measurements, but with larger diameters (⌀ 142 ± 25 nm; Figure ).…”
Section: Resultssupporting
confidence: 58%
“…For PANI, The bands at 1492 cm –1 and 1571 cm −1 are due to the absorb vibration of C=C of benzene structure and C−C of quinone rings, respectively . The band around at 1300 cm –1 and 1148 cm –1 correspond to C−N stretching near the quinone rings and the stretching of NH + in doped PANI, respectively; The bands at 825 cm –1 and 740 cm –1 are belong to the aromatic C−H bending in the 1,4‐disubstituted aromatic ring . It can been revealed that PANI film has been successfully coated on the surface of PEDOT, evidenced by the arising of peak around at 1300 cm –1 (proving of the existence of element N in PANI) in the FT‐IR spectra of PEDOT/PANI.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was carried out in a pH range between 1 and 4. The spectroscopic characteristics were, like the PANI, obtained enzymatically, however, the electrical conductivity decreased Wang Q. et al (2018) . Our group has also contributed to the biomimetic synthesis field using catalyst supports ( Tierrablanca et al, 2010 ).…”
Section: Introductionmentioning
confidence: 87%
“…reported the biomimetic synthesis of PANI using ferrocene, a sandwich-type metallocene widely used in organometallic chemistry. To our knowledge, this investigation was the first reporting ferrocene-based enzymomimetic polymerization, leading to a new pathway for the synthesis of CSP Wang Q. et al (2018) .…”
Section: Introductionmentioning
confidence: 88%